Analisis Minyak Atsiri Bunga Melati menggunakan Kromatografi Gas-Spektroskopi Massa (GC-MS) - Ni Made Sukma Sanjiwani Sanjiwani; Sudiarsa I Wayan; Ayu Mirah Mariati Ni Putu (Emasains : Jurnal Edukasi Matematika dan Sains, 2022)
Abstract : It has been done Analysis Oil Jasmine Flower Essentials with Gas Chromatography- Mass Spectroscopy (GC-MS). Identification component group compound oil essential flower Jasmine researched with 2010 Shimadzu GCMS–QP tool . Condition operational tool namely : column DB-17MS, temperature column 70ºC and temperature 250ºC injection . Based on the results of GC - MS compounds group oil essential dominant in essential oils flower Jasmine are linalool, citronellal, beta-citronellol and trans-geraniol, the fourth compound the including group monoterpenoid compounds . On the spectrum ms linalool compound undergoes fragmentation with the release of (CH3 )•, ethyl group (C2 H5 )• and (C3 H7)• group . On the spectrum ms citronellal compounds undergo fragmentation with the release of (CH3 )•, groups (C3 H7 )•, groups (C5 H11)•, groups (C6 H13 )•, groups (C7 H15 )•, groups (C8 H17 )• and the group (C9H19)•. On the spectrum ms beta-citronellol compounds undergo fragmentation with the release of (CH3)•, (C2H5)• groups and (C3H 7 )•. On the spectrum ms trans-geraniol compounds undergo fragmentation with the loss of groups (C6 H13 )• and groups (C8 H17 )•. Keywords : Oil essential flower jasmine , GC-MS, linalool, citronellal, beta-citronellol and trans-geraniol